Surgical Treatment of Post Traumatic Spinal Instability with Anterior Components - Amel Djerbal; Samir Tebani; Kenza Badache; Yousria Akloul; Souhila Sadat; Dalila Zeghdoud; Reda Harrar (International Journal of Allied Medical Sciences and Clinical Research, 2024)
Our study focuses on unstable lumbar spine trauma. There were 16 cases: 8 cases had neurological lesions evaluated according to Frankel's classification From an anatomical point of view, these fractures associated serious bodily lesions and lesions of the posterior bone elements making them highly unstable. A neurotoxic fragment is often found. Canal stenosis was present in 6 cases. In 2 cases neurological lesions appear to be related to vascular disorders related to spontaneous displacement and reduction. Surgically, the first step has always been posterior stabilization associated with reduction and / or laminectomy. The previous approach was performed within two weeks 1. Overall, the clinical results were satisfactory with a consolidation and improvement of the Fränkel score with the exception of 2 cases seen at day 5 with Fränkel A lesions. In all cases kyphosis was reduced.